ASSESSMENT METHODS AND STRATEGIES OF PAIN AND STRESS MANAGEMENT IN NEONATAL INTENSIVE CARE UNITS - Alja Kavčič; Janja Gržinić (Slovenska pediatrija, 2024)

(untitled)
Pain is a negative sensation, produced by a certain stimulus, which consists of sensory perception and emotional processing. Neonates, especially preterms, have limited intrinsic pain regulation mechanisms and their central nervous system is in a critical period of maturation at the time of exposure. Therefore, short, and long-term consequences of pain are deleterious in this vulnerable population. Immediate effects of pain reflect in sympathetic activation, which impacts hemodynamics and brain perfusion. Long-term consequences manifest in macro-, micro-structural and metabolic brain changes, which lead to motor, cognitive and psychosocial dysfunction. Neonates in intensive care units are exposed to painful stimuli and environmental stressors, such as excessive noise and light daily, therefore our goal should be to minimize, recognize and appropriately treat pain and stress to improve outcome.